Análise de impacto sobre as cavernas e seu entorno no município de Laranjeiras, Sergipe - Donato, Christiane Ramos (2011)
The main goal of this research was analyse the degree of conservation of the caves locates in the Laranjeiras district. The characterization of the hypogeal fauna was made following Gomes et al. (2000), Hunt & Millar (2001) and Silva (2006); and the flora, near the cave entrance, following Fidalgo & Bononi (1984). The statistical analyses were made in free softwares: Mata Nativa 2, R estatística 2.12.1 and PAST 2.02. This research proposed an avaliation protocols for measure environments impacts in caves. The results show that the Atlantic forest fragments near the caves was in a second stage of succession, in contrast to what is proposed by the law. There are a high beta diversity and low fauna similarities between the studied caves, so each cave is a unique ecosystem. In every cave was saw environments impacts, and in two of them is in a high vulnerability. However the prioritization for conservation/restoration of these caves was made by your intrinsic characteristics, and no by the environment impacts associated. Another researches are necessary to know better the speleological patrimony of the Laranjeiras district (and of the state of Sergipe), at the same time is necessary to know how the relationship between the communities that lived near and the conservation of these caves.